Spanish now. Level 1 - Silverstein, Ruth J.; Pomerantz, Allen; Wald, Heywod (Hauppauge, N.Y. : Barron's, 2005)
Includes sections on structure, verbs, vocabulary, idioms, reading and listening comprehension, writing and Hispanic culture.
Includes index.
All age.
Keywords: Spanish language -- Grammar; Spanish language -- Textbooks for foreign speakers -- English